Analysis of Students' Critical Thinking Skills in Solving Mathematics Problems on Pythagoras - Heinrich Osvaldo Ndahawali; Sri Hariyani; Nur Farida (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2020)
This study aims to describe the critical thinking skills in solving math problems. The approach used in this research is qualitative research with descriptive research type. The research subjects were 32 students. The six interview subjects were divided into three levels of critical thinking, namely 2 high categories, 2 medium categories and 2 low categories. Data collection procedures are tests of critical thinking skills and interviews. Research data analysis refers to indicators of critical thinking, namely: interpreting, analyzing, evaluating and inferring. Student achievement on each indicator includes: 1) Percentage of students' ability to interpret the completion of the test questions by 65.5%; 2) The percentage of students' ability to analyze the completion of the test questions by 39.1%; 3) The percentage of students' ability to evaluate is 66.6%; and 4) Percentage of students' ability to infer by 40%. The ability of students to interpret a problem solving is good. Students have been able to write out what is known and asked in the problem correctly, but there are students who are less thorough and incomplete in writing the unit of distance. The ability of students to analyze problem solving is quite low. Students do not provide information on drawing illustrations. The ability of students in evaluating problem solving is good. Students are able to do the calculations correctly in accordance with the rubric of assessment. The ability of students to reference problem solving is low. Students are not used to writing the final conclusions of the answers obtained.